M&M's: Building Binary Software Components for Supporting Mobile-Agent Enabled Applications - Marques, Paulo (2002)
Mobile Agents provide a new promising paradigm for developing distributed applications. Nevertheless, although the basic concept has been around for some years and many agent platforms are available both from the industry and research community, there are currently few examples where the technology has been deployed in the real world. One important reason for this is that using the current available agent frameworks it is quite difficult to develop applications without having to center them completely on the agents and on the agent infrastructure. In this paper, we present the M&M project, taking place at the University of Coimbra. In this project, we are developing an extensive component-based framework that enables ordinary applications to use mobile agents in a flexible and easy way. By using this approach, applications can be developed using current object-oriented approaches and become able of sending and receiving agents by the simple drag-and-drop of mobility components. The framework was implemented using the JavaBeans component model and provides integration with ActiveX, which allows applications to be written in a wide variety of programming languages. By using this framework, the development of applications that can make use of mobile regents is greatly simplified, which can contribute to a wider spreading of the mobile agent technology.